2020
DOI: 10.21037/jtd-20-1792
|View full text |Cite
|
Sign up to set email alerts
|

Implications of pneumonitis after chemoradiation and durvalumab for locally advanced non-small cell lung cancer

Abstract: Background: Consolidation durvalumab improved overall survival (OS) in locally advanced non-small cell lung cancer (LA-NSCLC) treated with chemoradiotherapy (CRT) in the PACIFIC trial; however, pneumonitis was increased with durvalumab. We sought to examine real-world outcomes with the PACIFIC paradigm, especially factors associated with pneumonitis, using a multi-institutional review. Methods: Patients with LA-NSCLC treated with CRT followed by durvalumab from January 2017-February 2019 were identified at 2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“… 1 Recent data suggest that durvalumab rechallenge may be feasible in patients who develop pneumonitis. 5 Therefore, strong consideration of durvalumab rechallenge may be warranted in patients who develop pneumonitis who received less than 4 months of therapy. In addition, anti–programmed death-ligand 1 rechallenge has been found feasible across a range of immune-related AEs 6 , 7 ; therefore, given the substantial survival benefit of durvalumab, consideration should be given to rechallenge in patients who receive minimal therapy regardless of the specific AE.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Recent data suggest that durvalumab rechallenge may be feasible in patients who develop pneumonitis. 5 Therefore, strong consideration of durvalumab rechallenge may be warranted in patients who develop pneumonitis who received less than 4 months of therapy. In addition, anti–programmed death-ligand 1 rechallenge has been found feasible across a range of immune-related AEs 6 , 7 ; therefore, given the substantial survival benefit of durvalumab, consideration should be given to rechallenge in patients who receive minimal therapy regardless of the specific AE.…”
Section: Discussionmentioning
confidence: 99%
“…© 2021 American Association for Cancer clincancerres.aacrjournals.org Downloaded from grade 3-4 radiation pneumonitis with placebo. However, recent data show that in real world practice, grade 3 or higher pneumonitis is somewhat more frequent than this, at 6.5%, with 1.5% of patients experiencing fatal pneumonitis [34]. Other reports also showed increased rates of grade 3 pneumonitis with the addition of durvalumab, 14.3% compared to 3.4% that was reported in the PACIFIC trial.…”
Section: Response and Survivalmentioning
confidence: 93%
“…In the PACIFIC trial, any grade pneumonitis occurred at a rate of 33.9% in patients receiving durvalumab, with grade ≥ 3 pneumonitis occurring in 3.4% (24.8 and 2.6% in the placebo arm, respectively) [10]. Real-world data have reported frequencies of any grade and grade ≥ 3 pneumonitis of 20-80% and approximately 6%, respectively, with some studies reporting pneumonitis as a negative prognostic factor for survival [18,57,59,60]. Pneumonitis is a particularly concerning immune-related adverse event in patients with stage III lung cancer, as prior radiotherapy may act synergistically to increase its risk of occurrence [61].…”
Section: Immunotherapy: Treatment Initiation and Managementmentioning
confidence: 99%
“…To optimize patient outcomes, patient education on pneumonitis symptoms, and early diagnosis and intervention with an MDT, is essential [61]. Re-challenge with durvalumab can be considered after resolution of symptoms; however, guidelines on safely re-challenging are limited [60]. In two small retrospective studies, re-challenge with durvalumab was shown to be feasible, leading to pneumonitis recurrence in 14 and 29% of patients [59,60].…”
Section: Immunotherapy: Treatment Initiation and Managementmentioning
confidence: 99%
See 1 more Smart Citation